Pengaruh Penerapan Model Game-Based Learning dengan Platform CodeCombat untuk Meningkatkan Pemahaman Pemrograman Siswa MTsN 2 Solok - Nabiilah, Rifqah Nuha; Zaus, Mahesi Agni (Lembaga Yasin AlSys, 2025)
Algorithms and Programming play an important role in developing computational thinking skills; however, students’ understanding of this subject, including at MTsN 2 Solok, remains relatively low. This study aims to analyze the effect of applying the Game-Based Learning model using the CodeCombat platform on improving students’ programming comprehension. The research employed a quantitative quasi-experimental design, involving two classes—VIII A and VIII B—selected through purposive sampling, each consisting of 32 students as the experimental and control groups. Data were collected through validated multiple-choice pre-tests and post-tests, then analyzed using the paired sample t-test and independent sample t-test after meeting normality and homogeneity assumptions. The results show a significant improvement in programming comprehension in the experimental class after game-based learning with CodeCombat, with an average post-test score of 80.62 compared to 62.63 in the control class. It is concluded that the application of Game-Based Learning with CodeCombat is effective in enhancing students’ programming comprehension. The implications of this research include enriching the literature on game-based learning in informatics education and providing recommendations for educators to utilize interactive media in programming instruction, while also opening opportunities for further studies on the effects of duration and intensity of educational game use on learning outcomes.